(untitled) (Nexus International Journal of Science and Education, 2024)
The study navigated the relationship between the work-school environment and teachers’ productivity in Tugbok District, Davao City. A non-experimental quantitative research design was employed, and data were collected from 250 elementary school teachers through stratified sampling. Modified survey questionnaires assessed the work-school environment and teacher’s productivity. The findings revealed an extensive work-school climate in Tugbok District, Davao City, regarding the physical condition and good employee management. Likewise, the extent of the teachers’ productivity in Tugbok District, Davao City. In terms of Compensation, work motivation, and self-discipline was extensive. There was a relationship between the work-school environment and teachers’ productivity. All the domains in the work-school environment significantly influenced Teachers’ Productivity. This provides empirical evidence that the indicators enumerated under Teachers’ Productivity could account for and explain the variability of the work-school environment. These findings support the existing literature highlighting the importance of a good and functional workplace in understanding the perspectives of teachers’ working conditions. Thus, the teacher will have a positive self-image, value his job, and give it his all. The study provides valuable insights for the Department of Education, Administrators, Teachers, and future researchers to understand better the importance of those above in fostering a much better learning community for students and everyone in it.